Reduction of Peripheral Blood iNKT and γδT Cells in Patients With Parkinson's Disease: An Observational Study - Zhou, Chao; Zhou, Xinhua; He, Dan; Li, Zhen; Xie, Xufang; Ren, Yue (Frontiers in Immunology, 2020)
Objective: To investigate the frequencies and numbers of invariant natural killer T (iNKT) cells and γδT cells in the peripheral blood of patients with the Parkinson's disease (PD), and to examine their association with the PD severity. Methods: Peripheral blood samples from 47 PD patients (PD group) and 47 age-matched healthy control subjects (HC group) were collected. The frequencies and the absolute cell numbers were analyzed by flow cytometry. Mann-Whitney U test was used to test the difference between two groups, where P<0.05 was considered as significant. An ordered probit regression method was used to examine the association of the iNKT and γδT cells with severity of PD. Results: Patients in the PD group showed significantly lower frequencies (0.039% vs. 0.139%; P=0) and cell counts (308/mL vs. 1371/mL; P=0) of iNKT cells compared to the HC group. Moreover, the percentages and absolute numbers of γδT cells were significantly decreased in the PD group compared to the HC group (3.69% vs. 7.95% and 30/μL vs. 66/μL; P=0). The iNKT cells were significantly reduced in PD patients with higher Unified Parkinson’s Disease Rating Scale (UPDRS) scores or cognitive decline. Conclusions: Cell frequencies and absolute numbers of iNKT cells and γδT cells are significantly reduced in the peripheral blood samples of PD patients. Patients with high UPDRS scores or cognitive decline also showed significant reduction of iNKT cells. Our results suggest that iNKT cells and γδT cells may contribute to the development of PD.